Enhancing dewaterability of sewage sludge by the application of tween-20 during bioleaching: Performance evaluation and mechanistic study. Issue 7 (19th May 2018) - Gao, Jingqing; Shen, Yu; Li, Linshuai; Gao, Jianlei; Li, Yonghong; Liu, Chun; Chen, Jie
ABSTRACT: Dewatering is recognized as an important method for treating sewage sludge before its disposal. In this paper, the nonionic surfactant Tween-20 was used for the first time to improve the dewaterability of sewage sludge during bioleaching. The specific resistance to filtration (SRF), water content (WC) and bound water content (BW) of the sludge cake were used to evaluate sludge dewaterability. The results indicated that a 1 g/L Tween-20 dosage with an inoculum ratio of 20%, a S 0 dosage of 2 g/L and a FeSO4  · 7H2 O dosage of 10 g/L provided oxidation efficiencies up to 100% for Fe 2+ and 65.8% for S 0 . The SRF of the bioleached sludge decreased to as low as 0.81 × 10 12  m/kg from the initial 12.6 × 10 12  m/kg for raw sludge. A WC of 47.16% was achieved while 48.1% of BW was released during bioleaching. The results from this study indicate that adding of an appropriate amount of Tween-20 to sewage sludge is a promising method to enhance dewaterability by bioleaching.